The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.ejar.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Epipelic algal distribution in Ismailia Canal and the possible use of diatoms as bioindicators and a biomonitoring tool

Abstract: Ecology of Ismailia Canal and its branches were studied under a comprehensive program of the Freshwater and lakes Division, National Institute of Oceanography and Fisheries. Sixteen stations were selected quarterly in Ismailia Canal and its branches during 2011. Physical and chemical characters of water with surface sediment were sampled. Diatoms dominated the epipelon community, whereas chlorophyceae and cyanobacteria were rarely present. One hundred sixty-seven epipelic species were recorded. Diatoms were do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Therefore, it should be noted that the IDP index works both for natural and artificial substratum [75] river basins like the Sakarya, which is anthropogenically transformed and has high naturality. Previous data obtained in Egypt [76] has shown that indices created for similar conditions did not necessarily work in the same specific conditions, while the EPI-D index works very well in Mediterranean rivers [77,78]. One of the most important reasons for limiting the usage of diatom indices adopted from different climate zones (or developed for a specific purpose) is that there are great differences between species structures of diatom assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it should be noted that the IDP index works both for natural and artificial substratum [75] river basins like the Sakarya, which is anthropogenically transformed and has high naturality. Previous data obtained in Egypt [76] has shown that indices created for similar conditions did not necessarily work in the same specific conditions, while the EPI-D index works very well in Mediterranean rivers [77,78]. One of the most important reasons for limiting the usage of diatom indices adopted from different climate zones (or developed for a specific purpose) is that there are great differences between species structures of diatom assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…The principal aim of this study was to contribute to a response to this important question, in the above-mentioned literature and other papers, have been primarily based on light microscopyuncovered morphological traits, overlooking ultrastructural details which are crucial for precise species delineation, particularly in diatoms. Besides the interest in their spatio-temporal distribution and ecological niches, algal-and diatom-based environmental assessment (El-Naghy et al, 2006;El-Sheekh et al, 2010;Shaaban et al, 2012Shaaban et al, , 2015Abd El-Karim, 2014;Wołowski et al, 2017;Yusuf et al, 2018) and paleoenvironmental reconstructions (e.g., Zalat, 2003) have also been pursued in some studies. Given that Egyptian phycological investigations are mostly restricted to the River-Nile basin, lakes, pools, and agricultural drainages, the little-explored and untouched desert ecosystems in the Western and Eastern Deserts still await first or more intensive polyphasic studies, i.e.…”
Section: Introductionmentioning
confidence: 99%